The Effectiveness of Electronic Banking in Malaysia from the Customer’s Perspective - Diong, Jia Ming (2006)
This paper investigates whether Electronic Banking is effective from the customer’s perspective and to the extent to which they do, through the essential element of Electronic Banking which is determined as the customer’s electronic variable. Electronic Banking is not created to alter the method consumers spend their money, instead it make use of today’s technology to provide the consumer the option of avoiding the time-consuming, paper-based of traditional banking in order to manage finances more quickly and efficiently. Although many studies have been embarked on to examine issues in the wider context of Electronic Banking and customer loyalty, detailed research in the area of Electronic Banking issues and the effectiveness from the customer’s perspective has been rather limited. Using the web-based survey methodology, this study intends to fill the gap in the literature by focussing on the effectiveness of Electronic Banking in Malaysia from the customer’s perspective. Discoveries of this study will be of use for the banking industry in measuring the impact of information technology and to prepare appropriate strategies for structuring customer loyalty thereby enabling them to retain customers. Drawing on the research of Pikkarainen et al. (1989) and related studies, this paper uses the factors that influence the electronic banking acceptance in the light of Technology Acceptance Model (TAM).